Impact of social media influencers on brand awareness: A study on college students of Kolkata - Jyoti Dutta; Manali Bhattacharya (Communications in Humanities and Social Sciences, 2023)
Social networks have undoubtedly emerged as a powerful mode of communication in which their platforms allow people to set up a personal page or profile to which they could post updates regarding product/service reviews. This has led to the rise of human idols referred to as Social Media Influencers (SMIs) allegedly operating as ‘hidden persuader’ who informs, motivates, and persuades their audience. Influencer marketing is an indispensable aspect of contemporary life, often held as a creative and glamorous area, to create an impact on Generation Z and society in general. Social media is in vogue, enables real-time interaction, and has considerably impacted people's lives worldwide. Every day social media users are confronted with multiple products and services through unsolicited pop-ups, telemarketing, and streaming, which lead to impulse lead purchases. With its ubiquitous and networkable features, social media is popular among youth to share and interact in a virtual environment. This study aims to examine how brand awareness and social media influencers affect the consumers' intention to purchase. Brand awareness reached by influencer appeal is positive and growing faster than digital advertising an insignificant influence on purchase decisions among college students of Kolkata. The findings of this study confirmed the widespread beliefs that media social influencers have a real and favorable influence on raising brand awareness; however, leveraging social media influencers to affect brand recall and awareness did not have a significant impact.